An improved design of a passive sampler for polar organic compounds based on diffusion in agarose hydrogel - Urík, Jakub; Vrana, Branislav (Environmental science and pollution research international, 2019)
Passive samplers based on diffusive gradients in thin hydrogel films (DGT) were recently modified for sampling of polar organic compounds in water. However, since the sampling rates of the commonly used DGT design with the surface area of 3.1 cm2 are low, we propose to increase them by applying a two-sided design with a larger sampling surface area of 22.7 cm2. The sampler design consists of two sorptive hydrogel disks compressed between two diffusive hydrogel disk layers strengthened by nylon netting and held together by two stainless steel rings. Sorbent/water distribution coefficients (KSW) were determined, and the sampler was calibrated for monitoring 11 perfluoroalkyl substances and 12 pharmaceuticals and personal care products in water at laboratory conditions using a closed system with artificial flow generated by submersible pumps. A field performance test was conducted at five locations in the Morava River basin in Czech Republic. The median value of laboratory-derived sampling rates was 43 mL day-1 with extreme values of 2 mL day-1 and 90 mL day-1 for perfluorotridecanoic and perfluoroheptanoic acids, respectively. The log KSW values of tested compounds ranged from 3.18 to 5.47 L kg-1, and the estimated halftime to attain sampler-water equilibrium ranged from 2 days to more than 28 days, which is the maximum recommended exposure period, considering potential issues with the stability of hydrogel. The sampler can be used for assessment of spatial trends as well as estimation of aqueous concentration of investigated polar compounds.
Keywords: sefarosa; Diffusive gradients in thin films (DGT); Water monitoring; Polar organic compounds; voda; Česká republika; hydrogely; fluorokarbony; Organic Chemicals; Water; řeky; Czech Republic; Rivers; chemické látky znečišťující vodu; kyseliny heptylové; Passive sampling; Heptanoic Acids; Fluorocarbons; Water Pollutants, Chemical; Hydrogels; Hydrogel; difuze; Diffusion; organické látky; Sepharose